Hydrothermal Synthesis, Characterization and Biocompatibility Study of Thermally Modified Hydroxyapatite Nanoparticles - Chavan, Amol B.; Gawade, Sanjaykumar S.; Maldar, Parvejha S. (Asian Journal of Chemistry, 2026)
The hydrothermal synthesis of hydroxyapatite nanoparticles (HANPs) followed by comprehensive characterization using XRD, SEM, TEM, XPS, FTIR, Raman spectroscopy, and cytotoxicity analysis, enabling systematic evaluation of the effects of hydrothermal processing and post-synthesis heat treatment on the structural properties and biological response of HANPs were carried out. In this work, calcium nitrate tetrahydrate, ammonium dihydrogen phosphate, and ammonia solution were used as precursors. The synthesized HANPs were subsequently heat-treated at 200 ºC, 300 ºC and 400 ºC, and the treated samples were evaluated for phase composition, structural morphology and cytotoxicity. The synthesized HANPs exhibited a hexagonal crystal structure with an average crystallite size of 24.87 nm and the cytotoxicity results confirmed their biocompatibility. These structural and biological characteristics indicate that HANPs prepared through this method are promising biomaterials for potential biomedical applications, while the synthesis approach remains simple and cost-effective.